Pemberdayaan UMKM Berbasis Potensi Daerah di Jalur Lintas Selatan (JLS) Sine - Ardaningrum, Nandita; Nasrin, Ewita; Dwi Firnanda, Vicki Meilia; Almanikma, Mayza; Azizah, Siti Faizatul; Nurulhasan, Adinda Yasinta; Diniati, Bintis Ti'anatud (Universitas Pahlawan Tuanku Tambusai, 2025)
Micro, Small, and Medium Enterprises (MSMEs) Refer to productive business units that are run independently and have a major role in driving local economic growth. One of the potential sectors in the South Coastal Route (JLS) Sine area is the fishing sector. The catch from fishermen is the main commodity processed and marketed by MSMEs, thus creating business opportunities and improving the economy of the surrounding community. The purpose of this empowerment activity is to increase awareness of business actors regarding the importance of utilizing local potential, as well as identifying the challenges faced by MSMEs in managing and developing businesses based on marine potential. The results of this activity show that MSMEs in JLS Sine have a strategic role in strengthening the local economy. Through mentoring and education, MSMEs begin to realize the importance of exploring the potential around them, recognizing the business challenges faced in running a business and starting to find solutions to overcome them, such as realizing cooperation and increasing their own capacity. In addition, MSMEs also increasingly understand how to develop businesses in a focused and sustainable manner.